Dynamic Simulation Of Phenol Adsorption Using Microwave Induced Coconut Shell Activated Carbon - Lim, Kai Wen (Universiti Sains Malaysia, 2021)
Coconut shell is a cheap, sustainable, and abundant resources in Malaysia as a raw material for making the activated carbon to be used as adsorbent in the adsorption process. In this study, the adsorption performance of the microwave induced coconut shell activated carbon is tested on the continuous adsorption of phenol by using ASPEN Adsorption software. The effects of the process parameters such as flow rate, initial phenol concentration and adsorbent bed height to the adsorption performance are investigated and the results showed that those 3 parameters have a significant effect on the adsorption performance. The adsorption performance of the phenol by using the microwave induced coconut shell activated carbon is evaluated by using the breakthrough time and the breakthrough adsorption capacity. The phenol adsorption performance is studied for both experiment and simulation and the results show a similar trend on the varying of process parameters. Higher amount of phenol is adsorbed on the activated carbon when the feed flow rate is lowered. In the other hand, the amount of phenol adsorbed also increased as the initial phenol concentration and bed height increased. The breakthrough behaviour of phenol adsorption is predicted by using three dynamic models which are Thomas model, Yoon-Nelson model and Adams-Bohart model. All three models are capable in providing a good fit to both the experimental data and simulation results based onthe high r2 values.